2020
DOI: 10.1371/journal.pntd.0008219
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of kdr haplotypes in worldwide populations of Aedes aegypti: Independent origins of the F1534C kdr mutation

Abstract: Aedes aegypti is the primary vector of dengue, chikungunya, Zika, and urban yellow fever. Insecticides are often the most effective tools to rapidly decrease the density of vector populations, especially during arbovirus disease outbreaks. However, the intense use of insecticides, particularly pyrethroids, has selected for resistant mosquito populations worldwide. Mutations in the voltage gated sodium channel (Na V) are among the principal mechanisms of resistance to pyrethroids and DDT, also known as "knockdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 48 publications
10
57
0
Order By: Relevance
“…Recent studies carried out in the Asian region showed high frequencies of 1534C mutant allele when compared with the frequency of 989P + 1016G mutant alleles reported [41]. It has been also suggested that F1534C mutation have multiple origins and in Asian populations V1016G mutant haplotype and S989P + V1016G haplotype have emerged from a F1534C haplotype [42]. Our analysis of Ae.…”
Section: Discussionmentioning
confidence: 46%
“…Recent studies carried out in the Asian region showed high frequencies of 1534C mutant allele when compared with the frequency of 989P + 1016G mutant alleles reported [41]. It has been also suggested that F1534C mutation have multiple origins and in Asian populations V1016G mutant haplotype and S989P + V1016G haplotype have emerged from a F1534C haplotype [42]. Our analysis of Ae.…”
Section: Discussionmentioning
confidence: 46%
“…The kdr Na V R1 allele (1016Val + 1534Cys kdr ) was present in all Brazilian populations evaluated here, and fixed in one of them. This was probably the first kdr allele to spread in Latin America 20 and is present in at least two haplotypes of independent phylogenetic origins 17 . kdr Na V R2 (1016Ile kdr + 1534Cys kdr ) confers a higher level of resistance to pyrethroids compared to Na V R1 17 , which may explain why Na V R2 frequency is rapidly increasing compared to the wild-type Na V S and kdr Na V R1 alleles, as observed in Ae.…”
Section: Discussionmentioning
confidence: 95%
“…aegypti populations worldwide. The Phe to Cys substitution in the 1534 site (F1534C) is found in populations from the Americas, Africa and Asia, whilst the wild-type Val is substituted by Ile (V1016I) in the 1016 site in American populations and by Gly (V1016G) in Asian populations 17 20 . Additional alterations have also been reported, such as the Pro to Ser substitution in the 989 (P989S) and Val to Leu in the 410 position (V410L), respectively, in Asian and Latin American populations 4 , 17 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Ae. aegypti kdr haplotype analysis has confirmed that the Val1016/Cys1534 haplotype is found worldwide, while the Ile1016/Cys1534 haplotype is found only in the Americas (Cosme et al, 2020; Fan et al, 2020). This implies that both widely-dispersed and geographically constrained haplotypes contribute to the wide-spread pyrethroid resistance observed in Ae.…”
Section: Introductionmentioning
confidence: 83%